Uso da linguagem python no auxílio à aprendizagem de estatística descritiva na educação básica - Piaz, Marcelo Bragatto Dal (2023)
In today’s world, it is essential for people to have the ability to understand and comprehend the vast flow of information to which they are exposed on a daily basis. Therefore, the development of the skill of reading and interpreting numerical data, tables, and graphs is necessary. Regarding the teaching of Statistics, significant learning becomes crucial, given that society is becoming increasingly interconnected and generating more and more information. This work aims to offer strategies to approach Descriptive statistics topics using the Python programming language, seeking to contribute to a critical formation of students and provide new didactic tools to basic education teachers.